Application of mathematical model for assessment of river morphology : a case study of Titas river / Muhammad Anowar Saadat, Mir Abdus Subhan and Imran Khan - Saadat, Muhammad Anowar; Subhan, Mir Abdus; Khan, Imran (Universiti Teknologi MARA, Pulau Pinang, 2015)
Titas is one of the rivers of Bangladesh which has the complex Ganges- Brahmaputra-Meghna river system. 80% terrain of the country has been formed with massive sediment carried by these rivers. Titas River originates from the Meghna River and falls again in the same at downstream. The river has become silted up over the years creating water logging in wet season and scarce water during dry season. Gradually, the river became ineffective from all aspects such as irrigation, navigation, ecological demand, etc. Government of Bangladesh has taken up a project for re-excavation of Titas River to reduce these problems and to restore the previous condition of the river by attracting more flow from the Meghna River. The re-excavation work has to be sustainable with reasonable maintenance dredging and also should not pose threat for the river banks. Mathematical modelling of Titas River using MIKE software has been carried out to simulate the morphological development under different hydro-morphological scenario. Two separate models were developed to simulate the river hydraulics in fixed bed and morphology in movable bed condition for base and re-excavated condition. Simulated base condition has been calibrated with observed data but the predicted excavated condition was not possible to check with field condition as the envisaged excavation work has not been implemented yet. Consecutive three average year flood simulation showed that the re-excavated section would be filled up to 21% of the capital dredging volume which indicates the required yearly maintenance dredging volume. The stability condition of the river banks in reexcavated condition was also checked so that the excavation work can be performed without damaging public property from excavation induced bank erosion. The purpose of the study was to assist the implementing agency with suggestions required for intelligent dredging to make the project economic, feasible and acceptable to all.